1980
DOI: 10.1111/j.1528-1157.1980.tb04314.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Human Plasma GABA by Sodium Valproate

Abstract: gamma-Aminobutyric acid (GABA) was measured in the plasma of volunteers during subchronic treatment with sodium valproate (VPA). After 2 days of oral treatment with 300 mg VPA, t.i.d., the GABA concentration was increased to about 30% compared to 2 control days. This response was similar to that after 2 days of treatment with 600 mg VPA, t.i.d., whereas on the fourth day of treatment with the latter dose, a plasma GABA increase of about 90% was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(32 citation statements)
references
References 17 publications
1
30
0
1
Order By: Relevance
“…Moreover, it was previously suggested that VPA may influence thyroid function, because the drug combinations that cause the most marked reductions in thyroid hormones and the most marked increases in TSH are those comprising VPA and an enzyme-inducer, notably CBZ (19,29). The high levels of serum basal TSH observed in VPA monotherapy patients and CBZ-VPA combination-therapy patients may be due to the y-aminobutyric acid (GABA) ergic properties of VPA (42), because GABA inhibits somatostatin release, and somatostatin inhibits TSH secretion Our PB-treated series is the largest reported to date in a pediatric population, although the childadult series of Tanaka et al (24) was larger. We observed decreases in the levels of T, and FT,, and no change in the level of TSH, as in previous studies (13,24,29).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was previously suggested that VPA may influence thyroid function, because the drug combinations that cause the most marked reductions in thyroid hormones and the most marked increases in TSH are those comprising VPA and an enzyme-inducer, notably CBZ (19,29). The high levels of serum basal TSH observed in VPA monotherapy patients and CBZ-VPA combination-therapy patients may be due to the y-aminobutyric acid (GABA) ergic properties of VPA (42), because GABA inhibits somatostatin release, and somatostatin inhibits TSH secretion Our PB-treated series is the largest reported to date in a pediatric population, although the childadult series of Tanaka et al (24) was larger. We observed decreases in the levels of T, and FT,, and no change in the level of TSH, as in previous studies (13,24,29).…”
Section: Discussionmentioning
confidence: 99%
“…g-Aminobutyric acid inhibits the release of somatostatin, which inhibits TSH secretion. 13 The causal association between valproate and subclinical hypothyroidism has been suggested by Eirís-Puñal and colleagues. 4 They observed normalization of elevated TSH levels after the valproate was changed to ethosuximide in one case.…”
Section: Prevalence Of Subclinical Hypothyroidism In Children With Epmentioning
confidence: 94%
“…Berrettini et al 98 reported that lithium increased the CSF and plasma levels of GABA in euthymic bipolar patients, although they did not replicate these findings in a second larger study. 102 Valproate has been shown to increase plasma GABA levels in human individuals, [208][209][210] suggesting that it enhances brain GABA activity. Petty et al 131 reported that higher pretreatment GABA plasma levels predicted response to valproate in acute manic patients, and did not correlate with symptom severity.…”
Section: Gabaergic Modulation In the Treatment Of Mood Disordersmentioning
confidence: 99%